Obesity Prevention Program in Childcare Centers: Two-Year Follow-Up. Issue 6 (November 2017) - Natale, Ruby A.; Messiah, Sarah E.; Asfour, Lila S.; Uhlhorn, Susan B.; Englebert, Nicole E.; Arheart, Kristopher L.
Purpose: To assess the impact of an early childhood obesity prevention intervention "Healthy Caregivers–Healthy Children" (HC2) on dietary patterns and body mass index percentile (PBMI) over 2 school years. Design: Randomized controlled trial. Setting: Childcare centers. Participants: Low-income families. Intervention: Intervention centers (N = 12) received HC2 which consisted of (1) menu modifications, (2) a healthy eating and physical activity curriculum for children, and (3) a parent curriculum for healthy meal preparation, reinforced through a role-modeling curriculum. Control centers (N = 16) received an injury prevention/safety intervention. Measures: Child PBMI and parent report of child's consumption of fruits/vegetables and unhealthy food. Analysis: Confirmatory factor analysis verified the psychometric properties of factor scores for children's consumption of fruits/vegetables and unhealthy food. Growth curve analysis assessed the impact of HC2 on change in consumption of fruits/vegetables and unhealthy food and PBMI over 2 school years. Results: Children in the intervention group (n = 754) had a negative slope (β = −1.95, standard error [SE] = 0.97, P = .04), indicating less increase in PBMI versus control children (n = 457). Stratified analyses showed that obese children in the intervention arm had a significantly higher increase in fruit/vegetable consumption versus control group obese children (β = 0.24, SE = 0.08, P = .003). Conclusion: The HC2 intervention resulted in the maintenance of healthy PBMI over 2 preschool years among low-income multiethnic children. These findings support efforts to implement healthy weight programs in the childcare setting.